Morphological and phenological characteristics of petunia (Petunia hybrida Vilm.) flowering - Asri Ferianti Sareh; Pinta Murni; Ervan Johan Wicaksana (Universitas Islam Negeri Sumatera Utara, 2023)
Petunia hybrid Vilm. is an ornamental plant that has the potential to be developed because its flowering period does not know the season and comes with various motifs and flower colors that can add cultivation and commercial value. Information on the morphological characteristics of flowers and flowering phenology is the basis for their development. The aim of this study was to characterize the morphological structure of flowers and observe a series of phases in flower development stages associated with environmental factors. This research was conducted in the sustainable twin housing complex in the city of Jambi on March 25–May 27, 2022, and the data obtained was analyzed descriptively, qualitatively, and quantitatively. The results of flowering phenology observations showed that petunia flower development occurred over an average period of 37 days. Based on the characterization of the morphological structure of the flower, the average length is 72 mm and the diameter is 42 mm. It is categorized as a complete flower because it has a main organ consisting of five petals with an average diameter of 42 mm, five petals with an average length of 14 mm, and an average diameter of 16 mm. Furthermore, the genitals of the flower, namely the stamens, are five in number, and there is one pistil in each flower.